NILAI-NILAI EDUKATIF DALAM WAYANG PURWA LAKON âRABINE BAMBANG WIJANARKOâ - Wahyuningsih, Agung Tri (Jurnal Pengembangan Pendidikan, 2011)
Abstract. Puppet show becomes alast option for teenagers when they get some alternative shows. This is a verypathetic phenomenon as the generation has no longer been interested to theirown asset. Thus, people who love and care about puupet should find a way tomake puppet show live because in the story we can get great life values andmoral teaching. A nation is strong when it has good and firm characters. Thisarticle talks about some educative values which have relations to values ofpoliteness and firm and strong will of the main characters of the puppet showentitled âRabine Bambang Wijanarkoâ. The educative values are traced andanalized from dialogues of the main characters with the supporting characters